Resumption of Antiplatelet Therapy after Major Bleeding - Geisler, Tobias; Poli, Sven; Huber, Kurt; Rath, Dominik; Aidery, Parwez; Kristensen, Steen D.; Storey, Robert F.; Ball, Alex; Collet, Jean-Philippe; Berg, Jurriën ten (Thrombosis and Haemostasis, 2022)
Major bleeding is a common threat in patients requiring antiplatelet therapy. Timing and intensity with regard to resumption of antiplatelet therapy represent a major challenge in clinical practice. Knowledge of the patient's bleeding risk, defining transient/treatable and permanent/untreatable risk factors for bleeding, and weighing these against thrombotic risk are key to successful prevention of major adverse events. Shared decision-making involving various disciplines is essential to determine the optimal strategy. The present article addresses clinically relevant questions focusing on the most life-threatening or frequently occurring bleeding events, such as intracranial hemorrhage and gastrointestinal bleeding, and discusses the evidence for antiplatelet therapy resumption using individual risk assessment in high-risk cardiovascular disease patients.
Keywords: bleeding; antiplatelet therapy; resumption of antiplatelet therapy; intracranial bleeding; gastrointestinal bleeding; aspirin; dual antiplatelet therapy